Studi Tingkat Kepuasan Pasien Rawat Inap Terhadap Mutu Pelayanan Kesehatan RSUD Takalar - Fitriah Handayani; Diah Mutiarasari (Biology Department, Mathematics and natural science, Tadulako University, 2010)
The study is devoted to investigating lodge patients satisfaction level of health service quality from tangible, reliability, responsiveness, emphaty, and assurance dimension. It is descriptive survey method wich used quisioner as instrument for data collecting. The number of sample was 51 respondens whoom nursing at Public Region Hospital Takalar, selected by purposive sampling. The research show patient satisfaction level from tangible is good (79,65%), reliability is good (77,13%), responsivenees is good (77,01%), emphaty is good (74,37%), assurance is good (70,92%). The conclusion lodge patients satisfaction level of healthy service quality is ”good” (75,82%). Key words: Satisfaction level, health service quality, lodge patients.